Cysteine-Rich Secretory Proteins (CRISP) are Key Players in Mammalian Fertilization and Fertility - Gonzalez, Soledad N.; Sulzyk, Valeria; Weigel Muñoz, Mariana; Cuasnicu, Patricia S. (Frontiers in Cell and Developmental Biology, 2021)
Mammalian fertilization is a complex process involving a series of successive sperm-egg interaction steps mediated by different molecules and mechanisms. Studies carried out during the past 30 years, using a group of proteins named CRISP (Cysteine-RIch Secretory Proteins), have significantly contributed to elucidating the molecular mechanisms underlying mammalian gamete interaction. The CRISP family is composed of four members (i.e. CRISP1-4) in mammals, mainly expressed in the male tract, present in spermatozoa and exhibiting Ca2+ channel regulatory abilities. Biochemical, molecular and genetic approaches show that each CRISP protein participates in more than one stage of fertilization (i.e. cumulus penetration, ZP-binding, ZP penetration, gamete fusion) by either ligand-receptor interactions or the regulation of several capacitation-associated events (i.e. protein tyrosine phosphorylation, acrosome reaction, hyperactivation, etc) likely through their ability to regulate different sperm ion channels. Moreover, deletion of different numbers and combination of Crisp genes leading to the generation of single, double, triple and quadruple knockout mice showed that CRISP proteins are essential for male fertility and are involved not only in gamete interaction but also in previous and subsequent steps such as sperm transport within the female tract and early embryo development. Collectively, these observations reveal that CRISP have evolved to perform redundant as well as specialized functions and are organized in functional modules within the family that work through independent pathways and contribute distinctly to fertility success. Redundancy and compensation mechanisms within protein families are particularly important for spermatozoa which are transcriptionally and translationally inactive cells carrying numerous protein families, emphasizing the importance of generating multiple knockout models to unmask the true functional relevance of family proteins. Considering the high sequence and functional homology between rodent and human CRISP proteins, these observations will contribute to a better understanding and diagnosis of human infertility as well as the development of new contraceptive options.